Machine Unit Dynamics Cotton Cleaner Section With New Drive Circuit (Eurasian Journal of Engineering and Technology, 2025)
The article presents a modernized drive scheme for a cotton-ginning unit of installation cotton-ginning-complex (ICGC). The computational and mathematical models of machine units of the cleaner with mechanisms of sawing, peeling, and transporting drums have been calculated and completed. Based on the numerical solution of the problems of the dynamics of machine units, the regularities of the movement, graphic dependences and parameters of the working bodies obtained considering on the given calculations. Analyzes of the constructed graphical dependencies with justified and recommended specific values of the parameters of the working bodies and belt drives in the drive of the cotton cleaner with the recommended drive layout.